1999
DOI: 10.1097/00004872-199917040-00006
|View full text |Cite
|
Sign up to set email alerts
|

Power spectra of arterial pressure and heart rate in streptozotocin-induced diabetes in rats

Abstract: Our findings that the mid-frequency band variability of arterial pressure was reduced in diabetic patients suggest that sympathetic modulation of the cardiovascular system is impaired, corroborating other studies in such patients using this and other approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
32
1
11

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 31 publications
8
32
1
11
Order By: Relevance
“…[11][12][13][14][15] These methods are able to detect early abnormalities in the autonomic modulation of the cardiovascular system. [16][17][18][19] When evaluated in the time domain, the heart rate variability was reduced in chronic STZ-diabetic rats. 12,20 In another study, Fazan et al 19 observed reduction in the arterial pressure (AP) and heart rate (HR) variability, measured either as the standard deviation or by spectral analysis in chronic STZ-diabetic rats.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[11][12][13][14][15] These methods are able to detect early abnormalities in the autonomic modulation of the cardiovascular system. [16][17][18][19] When evaluated in the time domain, the heart rate variability was reduced in chronic STZ-diabetic rats. 12,20 In another study, Fazan et al 19 observed reduction in the arterial pressure (AP) and heart rate (HR) variability, measured either as the standard deviation or by spectral analysis in chronic STZ-diabetic rats.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] When evaluated in the time domain, the heart rate variability was reduced in chronic STZ-diabetic rats. 12,20 In another study, Fazan et al 19 observed reduction in the arterial pressure (AP) and heart rate (HR) variability, measured either as the standard deviation or by spectral analysis in chronic STZ-diabetic rats. In humans with DM, spectral analysis of HR disclosed significant changes in the cardiovascular variability in the frequency domain, which were apparent even before changes in all other standard cardiovascular parameters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkable autonomic dysfunction, particularly concerning the baroreflex, has been well described not only in diabetic patients (2,3), but also in chronic experimental models of diabetes (4,5,30). Short-term (5 days) diabetes also exhibited a dysfunction of the baroreflex in rats (7).…”
Section: Perspectivesmentioning
confidence: 99%
“…Dysfunction of the baroreflex has been well described not only in diabetic patients (2,3) and chronic models of diabetes (4)(5)(6), but also in short-term (5 days) experimental diabetes (7). Even though modest elevations of plasma glucose are associated with reduction of reflex control of heart rate in healthy volunteers (8,9), there is no report in the literature dealing with the acute effects of elevated blood glucose on the afferent arm (baroreceptors) of the arterial baroreflex in non-diabetic subjects.…”
Section: Introductionmentioning
confidence: 99%